Tracing the Dynamics of Land Corruption Investigations in Indonesia: A Case Study from Kuantan Singingi - Nasrizal Nasrizal; Zul Akrial; Riadi Asra Rahmad (Rule of Law Studies Journal, 2025)
Background; Corruption in Indonesia’s land sector undermines public confidence, with overlapping rules creating obstacles for fair investigation and prosecution. Aims; This research examines how land-related corruption is investigated by the District Prosecutor’s Office in Kuantan Singingi. It aims to evaluate the adequacy of the legal framework while also identifying the main difficulties encountered in practice. Methods; The study applies a normative juridical method combined with a case study approach. Sources include statutory regulations, court rulings, and interviews with prosecutors and legal professionals. A qualitative analysis was carried out to assess how far the written laws align with the realities of enforcement on the ground. Result; The findings indicate that although Indonesia has comprehensive legal instruments to address corruption in land affairs, their application remains inconsistent. Investigators face problems such as limited institutional resources, challenges in proving manipulation of land certificates, and external pressures from political or economic actors. These issues tend to reduce prosecutorial effectiveness and slow the resolution of cases. Conclusion; The Kuantan Singingi experience illustrates wider systemic weaknesses in Indonesia’s anti-corruption framework. Building stronger institutional capacity, harmonizing land regulations, and ensuring transparency in prosecutorial practices are necessary steps to improve the integrity and effectiveness of land corruption investigations.